SOX10 and The Tendency of Perineural Invasion in Salivary Gland Adenoid Cystic Carcinoma - Safnita, Dewi; Hilbertina, Noza; Mulyani, Henny; Tofrizal; Khambri, Daan; Yetti, Husna (Majalah Patologi Indonesia, 2025)
Background Adenoid cystic carcinoma is a malignant salivary gland tumor with unique features, including slow growth, progressive, poor prognosis, recurrence propensity, and perineural invasion tendency. SOX10 is a transcription factor expressed in the majority of tumors. SOX10 overexpression was hypothesized to play an important role in tumor-stroma interactions, especially perineural invasion and histopathological patterns.   Method A cross-sectional study was performed using 30 blocks of formalin-fixed embedded specimens previously diagnosed as salivary gland adenoid cystic carcinomas. Perineural invasion and histopathological patterns were evaluated followed by immunohistochemical staining to evaluate SOX10 expression. The staining intensity and proportion of positively stained cells in both tumor and stroma cells were grouped into high and low expression levels. Chi-square tests were used for statistical analysis.   Result The cribriform pattern was the most common histopathological pattern in both high and low SOX10 expression. The majority of tumors with high SOX10 expression (66.67% in stroma cells and 73.33% in tumor cells) were found to have more perineural invasion.   Conclusion There was a tendency for perineural invasion in tumors with high SOX10 expression, although this was not statistically significant. There was no significant association between SOX10 expression and histopathological pattern.